GAYA KEPEMIMPINAN KYAI LUKMAN AL-KARIM DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM (Studi Kasus di Pondok Pesantren Bahrul Maghfiroh Malang) - Rusmini, Rusmini (Universitas Islam Negeri Raden Intan Lampung, 2015)
LEADERSHIP STYLE OF KYAI LUKMAN AL-KARIM IN THE DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTION: A CASE STUDY IN PESANTREN BAHRUL MAGHFIRAH, MALANG: The leadership is not something that can only be learned and researched. Even in leadership, many types can be found; character and the most protrude leadership action from a person who has an important role in his achievement to lead his institution. This research was conducted through field research using qualitative model. Researcher inspected the opinions of Kyai Lukman thinking in his efforts to develop and advance his pesantren. The result of this research is: to lead and defend the existence of his Islamic boarding school that he runs by himself, Kyai Lukman applies many strategies as follow: First, Kyai Lukman’s strategy in managing the educational funding. Kyai Lukman uses several kinds of method to fund the educational activities in his institution; they are self-funding and donation from the income of pesantren profit centers. Kyai Lukman increases the quality of laborers in pesantren Bahrul Maghfiroh by giving the examplary attitude of wara‘, uswatun hasanah (good example) and riyadloh (tirokat) to all students, all laborers and all teachers (asatizh). Kyai Lukman also expanded the curriculum of teaching in his pesantren. Second, the types of Kyai Lukman’s leadership. From many perceptions, the researcher could classify that Kyai Lukman has charismatic, transformational, and visionary leader attitude.